2021
DOI: 10.1002/agj2.20820
|View full text |Cite
|
Sign up to set email alerts
|

Maize response to combined heat and water stresses under varying growth conditions

Abstract: Identificationof agronomic practices that can ameliorate the negative effect of combined heat and water stress on maize plants is vital in food security strategy. The objective of this study was to evaluate the effect of heat and water stress on the growth of maize (Zea mays L.) under variable growth conditions. A repeated greenhouse factorial experiment laid out in a completely randomized design with four replications was performed. The factors were maize variety, water stress, soil amendment, and soil type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This phenomenon was consistent across all treatment interactions. The decrease in yield as water stress increased in this study aligned with earlier reports [26][27][28]31] on the depressive impact of water stress on maize grain yield.…”
Section: Water Stress Maize Variety Soil Amendment and Soil Type Inte...supporting
confidence: 92%
See 2 more Smart Citations
“…This phenomenon was consistent across all treatment interactions. The decrease in yield as water stress increased in this study aligned with earlier reports [26][27][28]31] on the depressive impact of water stress on maize grain yield.…”
Section: Water Stress Maize Variety Soil Amendment and Soil Type Inte...supporting
confidence: 92%
“…In stress-prone environments, finding maize varieties that are tolerant to abiotic stresses will ensure food security. Maize varieties have been shown to have varying levels of tolerance to single or combined stress conditions [26,28,31], which is important for breeding and selection. The significant differences in maize yield attributes observed in this study can be attributed to their varying levels of tolerance to combined heat and water stress.…”
Section: Varietal Effects On Biological and Economic Yield Attributes...mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding highlights the importance of including heat stress tolerance in maize cultivar development [20]. It has been demonstrated that the response of maize plants to a single stressor differs from the synergistic effect of multiple stressors [3,4]. However, more research is needed to determine how these stressors affect maize progeny.…”
Section: Introductionmentioning
confidence: 89%
“…Plants, as sedentary organisms, respond to stress by modifying their physiological and genomic architecture [1]. These adjustments frequently result in decreased resource utilisation efficiency, which can result in yield losses ranging from minor to severe losses, or, in the worst-case scenario, plant death [2][3][4].…”
Section: Introductionmentioning
confidence: 99%